Brain cholesterol metabolism and Parkinson's disease. Issue 3 (25th January 2019) - Huang, Xuemei; Sterling, Nicholas W.; Du, Guangwei; Sun, Dongxiao; Stetter, Christina; Kong, Lan; Zhu, Yusheng; Neighbors, Jeffery; Lewis, Mechelle M.; Chen, Honglei; Hohl, Raymond J.; Mailman, Richard B.
ABSTRACT: Background: Circulating cholesterol levels have been linked to PD, but not directly to brain physiology. Objective: To assess whether brain cholesterol metabolism is related to PD. Methods: Sixty PD patients and 64 controls were recruited from an academic movement disorder clinic (2009–2012). Thirty‐five PD patients and 33 controls returned approximately 36 months later. Fasting plasma (S) 24‐OH‐cholesterol (brain‐derived cholesterol metabolite) and 27‐OH‐cholesterol (peripheral cholesterol metabolite) were quantified. Odds ratios for PD were derived from logistic regression models, adjusting for potential confounders. Relationships between the oxysterols and clinical measurements were explored using Spearman correlation coefficients. Results: Mean age of PD subjects was 63.8 ± 8.3 years and disease duration was 5.0 ± 5.4 years. Plasma (S) 24‐OH‐cholesterol levels were inversely associated with the odds of having PD, with an odds ratio of 0.92 (95% confidence interval: 0.87–0.97) for each 1‐ng/mL increase ( P = 0.004). Compared to the lowest tertile, the odds ratio was 0.34 (0.12–0.98) for the second tertile ( P = 0.045) and 0.08 (0.02–0.31) for the highest tertile ( P < 0.001). Higher (S) 24‐OH‐cholesterol levels also were correlated with better sense of smell (r = 0.35; P = 0.01). No significant associations were found between clinical measures and 27‐OH‐cholesterol, a peripheral cholesterol metabolite. Furthermore, (S) 24‐OH‐cholesterol levels were stable over time, whereas 27‐OH‐cholesterol decreased with time in both cases and controls. Conclusions: Results indicate that plasma (S) 24‐OH‐cholesterol (possibly reflecting brain cholesterol metabolism) is inversely linked to PD, is relatively stable over time, and may serve as a new biomarker for PD. Further investigation is necessary to determine the mechanistic and clinical implications. © 2019 International Parkinson and Movement Disorder Society